2013
DOI: 10.1111/ncmr.12002
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Behavior in Negotiations: The Moderating Role of Motivation on the Ability–Intentionality Relationship

Abstract: This article reports on a study of the effects of recognition of negotiable opportunities (ability) and self‐efficacy (motivation) on initiation behavior in negotiations, an often overlooked stage of the negotiation process. Three phases of the initiation process are examined—engaging, requesting, and optimizing—through three negotiation scenarios offering corresponding forced‐choice behavioral options. Results suggest that, overall, the recognition of negotiable opportunities and the interaction of recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Field research on negotiation, in which supervisors with real stakes in the negotiation outcomes provided performance ratings, was comparatively rare. The positive findings for these limited (2010) Intentions for assertive negotiation 86 .12 ns Volkema et al (2013) Propensity to initiate negotiations 115 .17 <.10 Locus of control Volkema & Fleck (2010) Propensity to initiate negotiations 86 .07 ns Volkema & Fleck (2010) Intentions for assertive negotiation 86 .18 ns Maximization and regret Iyengar et al (2006) Outcome satisfaction 548 À.27 <.01 Sharma et al 317 data suggest a source for the common intuition that personality matters in negotiation. In laboratory work, extraversion harmed performance in simple distributive tasks, but helped in the more complex integrative tasks (Barry & Friedman, 1998) that better reflect the reality of complex working relationships with long-term interdependence across multiple issues.…”
Section: Laboratory Studies Of Negotiationmentioning
confidence: 73%
See 1 more Smart Citation
“…Field research on negotiation, in which supervisors with real stakes in the negotiation outcomes provided performance ratings, was comparatively rare. The positive findings for these limited (2010) Intentions for assertive negotiation 86 .12 ns Volkema et al (2013) Propensity to initiate negotiations 115 .17 <.10 Locus of control Volkema & Fleck (2010) Propensity to initiate negotiations 86 .07 ns Volkema & Fleck (2010) Intentions for assertive negotiation 86 .18 ns Maximization and regret Iyengar et al (2006) Outcome satisfaction 548 À.27 <.01 Sharma et al 317 data suggest a source for the common intuition that personality matters in negotiation. In laboratory work, extraversion harmed performance in simple distributive tasks, but helped in the more complex integrative tasks (Barry & Friedman, 1998) that better reflect the reality of complex working relationships with long-term interdependence across multiple issues.…”
Section: Laboratory Studies Of Negotiationmentioning
confidence: 73%
“…Their conclusion that the choice effects were null served as the basis for others to advocate forgetting about individual difference effects. The effect sizes for simple choice games were actually stronger in many cases than for negotiations, just as the dichotomous choice to cooperate versus compete is Sharma et al 315 Volkema & Fleck (2010) Intentions for assertive negotiation 86 À.06 ns Volkema et al (2013) Propensity to initiate negotiations 115 .11 ns (continued)…”
Section: Simple Choice Studiesmentioning
confidence: 94%
“…Interindividual variables, such as characteristics of the negotiation partner (Bowles, Babcock, & Lai, 2007;Hederos Eriksson, & Sandberg, 2012) or power differences (Lammers, Galinsky, Gordijn, & Otten, 2008;Magee, Galinsky, & Gruenfeld, 2007;Small et al, 2007) were also shown to have an influence on the initiation of negotiation. Most previous research on initiation of negotiation focuses on intraindividual variables for predicting the decision to negotiate, such as gender (Babcock, Gelfand, Small, & Stayn, 2006;Greig, 2008;Hederos Eriksson & Sandberg, 2012;Schneider, Rodgers, & Bristow, 1999;Small et al, 2007), prior work experience, and the recognition of opportunities (Babcock et al, 2006;O'Shea & Bush, 2002), as well as on various personality variables (e.g., extraversion, neuroticism), norms, and attitudes (Harris & Mowen, 2001;Lee, 2000;Volkema & Fleck, 2012;Volkema, Kapoutsis, & Nikolopoulos, 2013).…”
Section: Antecedents and Consequences Of (Not) Initiating Negotiationsmentioning
confidence: 99%
“…Our common sense tells us that high-power parties will prevail in negotiations with low-power parties. A host of experimental studies confirms this notion, showing that low-power negotiators reach poorer negotiation outcomes: They claim less value ( De Dreu, 1995 ), are exposed to more attempts of intimidation ( De Dreu, 1995 ), are less willing to initiate negotiations ( Volkema et al, 2013 ), are less likely to make first offers (which generally yields a bargaining advantage; Magee et al, 2007 ), concede more ( Van Kleef et al, 2006 ), and – most importantly – end up with less profitable deals compared to their more powerful opponents ( Dwyer and Walker, 1981 ; Pinkley et al, 1994 ; Brett et al, 1996 ; Giebels et al, 2000 ; Kim and Fragale, 2005 ; Kim et al, 2005 ; Wolfe and McGinn, 2005 ).…”
Section: Low Power In Negotiationsmentioning
confidence: 90%